Diethylstilbestrol Action on Leydig Cell Function and Testicular Descent - Christopher R. Cederroth; Serge Nef (CHIMIA, 2008)
Exposure to environmental chemicals may adversely affect the endocrine system and male sexual development. Testicular descent is regulated hormonally by Leydig-cell derived testosterone and Insulin-like factor 3 (Insl3). While Insl3 is required for transabdominal descent by stimulating the contraction and growth of the gubernaculum, testosterone contributes to the involution of the suspensory ligament and mediates the inguinoscrotal phase of the descent. In rodents, prenatal exposure to estradiol or xenoestrogens such as diethylstilbestrol (DES) leads to cryptorchidism and is associated with a downregulation of Insl3 transcription. In this review, we summarize the molecular and endocrine events responsible for testicular descent and how fetal exposure to xenoestrogens can adversely affect it. Recent data suggest that in utero exposure to DES affects fetal Leydig cell endocrine functions, more precisely the steroidogenic function, Insl3 expression and testicular descent, via an ER?-dependent mechanism. The expression of Leydig-specific genes such as Insl3, Cyp17a1, Star and Renin1 were profoundly decreased upon exposure to E2 or DES but not affected in mutant testes lacking ER?. Whether these effects of ER? are mediated via its classical mode of action or through a non-genomic action remains unclear. Unraveling the molecular events inhibiting the endocrine functions of fetal Leydig cells through an ER?-dependent mechanism will provide important insights into the adverse effects of estrogenic exposure on the male urogenital system and testicular descent.